2018
DOI: 10.5530/ijper.52.3.50
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Contents, Oxidant/Antioxidant Potential and Heavy Metal Levels in Cyclocybe cylindracea

Abstract: Introduction: Mushroom species have been used for medical purposes and as nutrients since the old times. The present study aimed to determine phenolic content, antioxidant activity and heavy metal content of Cyclocybe cylindracea (DC.) Vizzini & Angelini mushroom. Materials and Methods: Phenolic contents were screened with HPLC devices. TAS, TOS and OSI values were determined using Rel Assay kits. Heavy metal content were determined with atomic absorption method using an atomic absorption spectrophotometer. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 27 publications
3
24
0
Order By: Relevance
“…The data may signify the investigations of different bioactive compounds from the plant tulsi species and the requisite level of activity (pharmacological) would be considered for further scrutiny to develop the potential drug molecule. Free radicals are the cause of several major disorders [17][18][19]. So, evaluation of antioxidant activity in Ocimum genotypes could result in the discovery of natural antioxidants with pharmacological and food value.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The data may signify the investigations of different bioactive compounds from the plant tulsi species and the requisite level of activity (pharmacological) would be considered for further scrutiny to develop the potential drug molecule. Free radicals are the cause of several major disorders [17][18][19]. So, evaluation of antioxidant activity in Ocimum genotypes could result in the discovery of natural antioxidants with pharmacological and food value.…”
Section: Resultsmentioning
confidence: 99%
“…Antioxidant is the first aids of a defense system against free radicals include a number of an antioxidant enzyme such as superoxide dismutase, peroxidase, guaiacol peroxidase, Polyphenol oxidase and a non-enzymatic antioxidant such as glutathione, ABTS, Flavonoids, total phenol content, FRAP, DPPH, total tannin content, ascorbic acid,and dietary antioxidant etc. [17][18][19]. Therefore through the project work determine the biochemical test on antioxidant activity of four tulsi genotype namely O. sanctum, O. tenuiflorum, O. gratissimum, and O. basilicum has done the comparative studies of antioxidant of four genotypes of Ocimum genius.…”
Section: Introductionmentioning
confidence: 99%
“…It was determined that the TAS value of Cyclocybe cylindracea was 4.325, the TOS value was 21.109 and the OSI was 0.488. 24 It was reported that the TAS, TOS and OSI values for Auricularia auricula and Trametes versicolor mushrooms were 1.010 and 0.820, 23.910 and 17.760, and 2.367 and 2.166, respectively. 25 TAS value of Lepiota cristata was 2.210, TOS value was 24.357 and OSI value was 1.103.…”
Section: Tas Tos and Osimentioning
confidence: 97%
“…Oxidative stress studies on different mushroom species reported that Cyclocybe cylindracea TAS value was 4.325, the TOS value was 21.109 and the OSI was 0.488. 15 It was reported that the TAS value of Pholiota limonella was 2.378, TOS value was 4.742 and the OSI value was 0.199. 16 In previous studies, it was determined that the TAS values of Auricularia auricula and Trametes versicolor were 1.010 and 0.820, TOS values were 23.910 and 17.760, and OSI values were 2.367 and 2.166, respectively.…”
Section: Tas Tos and Osimentioning
confidence: 97%